A case study on land subsidence occurrence in Joshimath, Uttarakhand - Nadhen Dolma; Tiyasha Tiyasha; Ashuvendra Singh (Discover Geoscience)
Abstract Natural and anthropogenic factors intensify the impacts of land subsidence, making it a pressing concern in Uttarakhand, India. This issue has become increasingly alarming, with recent estimates indicating that subsidence in some regions has increased by up to 50%. This review aims to provide a comprehensive analysis of land subsidence in Uttarakhand, with a specific focus on the crisis in Joshimath and other affected areas, such as Rishikesh. A detailed literature survey is conducted to elucidate the various manifestations of subsidence, including its impact on infrastructure, property, and environmental conditions. Joshimath, located in the Chamoli district, is of particular interest because of its position in seismic Zone V and its location in an ancient landslide zone. This study examines how subsidence in this area has led to infrastructure damage, property loss, and environmental degradation. In Rishikesh, issues such as heavy rainfall-induced subsidence have caused severe damage, including the collapse of buildings and the disruption of major highways. The review highlights key strategies that can prevent subsidence, such as enacting regulations on groundwater extraction, developing relocation plans for affected populations, and promoting water conservation and groundwater recharge. The goal of this paper is to find good ways to deal with and manage land subsidence in Uttarakhand by putting together existing research and suggesting steps that can be taken. This will help lessen its effects and stop it from happening again.